2021
DOI: 10.3390/biology10050400
|View full text |Cite
|
Sign up to set email alerts
|

GP88/PGRN Serum Levels Are Associated with Prognosis for Oral Squamous Cell Carcinoma Patients

Abstract: Progranulin (PGRN)/GP88 is a growth factor that is expressed in a wide range of tumor tissues. The secreted form is involved in various biological processes including proliferation and inflammation. In several tumor types, the serum GP88 level is associated with a patient’s prognosis; however, data for oral squamous cell carcinomas (OSCCs) have not yet been reported. We measured the serum GP88 levels in 96 OSCC patients by an enzyme immunosorbent assay (EIA) and correlated these data with clinicopathological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…In the opposite situation, where miR-107 was upregulated and PGRN was downregulated, the promotion of sensitivity of PC-3 cells to ionizing radiation was observed. Other available studies showed that PGRN serum concentration levels in patients with oral squamous cell carcinomas (OSCCs) are not associated with susceptibility levels to radiation therapy [150]. These findings could also suggest that PGRN-related pathomechanisms could be involved in tumour resistance to radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the opposite situation, where miR-107 was upregulated and PGRN was downregulated, the promotion of sensitivity of PC-3 cells to ionizing radiation was observed. Other available studies showed that PGRN serum concentration levels in patients with oral squamous cell carcinomas (OSCCs) are not associated with susceptibility levels to radiation therapy [150]. These findings could also suggest that PGRN-related pathomechanisms could be involved in tumour resistance to radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased GP88 protein levels in tumor tissues or increased GP88 protein levels in serum have been associated with increased aggressiveness and poor long-term prognosis in different cancers, including PCa [ 14 ]. In addition, an increase in GP88 protein has been described in relation to different cancer treatment resistance mechanisms [ 46 ], especially in endocrine-related tumors, such as letrozole and tamoxifen resistance in breast cancer cells [ 20 , 47 ] and chemoresistance to cisplatin in ovarian cancer cell lines [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the potential use of progranulin as a prognostic marker is also currently under investigation in other tumors, such as oral squamous cell carcinomas [ 133 ], advanced biliary tract carcinoma [ 134 ], gastrointestinal tumors [ 135 ] and papillary thyroid cancer [ 136 ].…”
Section: Progranulin In Solid Tumorsmentioning
confidence: 99%